Effects of smoking on hemoglobin and erythrocytes sedimentation rate and its association with ABO blood groups - R Thriveni (Journal of Indian Academy of Oral Medicine and Radiology, 2020)
Context: “Smoking causes variation in different parameters of blood like hemoglobin (Hb) and erythrocyte sedimentation rate (ESR).” Continuous exposure to carbon monoxide leads to the formation of carboxyhemoglobin, an inactive form of Hb with no oxygen-carrying capacity; carboxyhemoglobin also leads to shifting in the Hb dissociation curve on the left side, causing a reduction in the ability of Hb to deliver oxygen to the tissue. Aims: The aim of this study was to compare the effect of cigarette smoking on Hb and ESR between smokers and nonsmokers and its association with ABO blood groups. Settings and Design: A total of 100 subjects which included 50 smokers and 50 age-matched nonsmoker controls were included in this study. Material and Methods: 5 ml of venous blood was collected by venipuncture method and Hb was measured by cyanmethhemoglobin method, ESR by Westergren's method, and ABO blood grouping by slide method. Statistical Analysis Used: Statistical software SPSS version 20 (SPSS, Chicago, Illinois) was used. Student's t test was performed for parametric numerical data and Chi-square test was performed for nonparametric categorical data. A value of P < 0.05 was considered statistically significant. Results: The mean Hb was 16.83 g/dL in smokers and 14.42 g/dL in nonsmokers. The mean ESR was 5.36 mm in smokers and 3.96 mm in nonsmokers. Conclusions: A significant increase was seen in Hb and ESR in smokers when compared to nonsmokers. No significant association was seen between the ABO blood groups among smokers and nonsmokers.